Netrin-1 in the developing enteric nervous system and colorectal cancer - Ko, S.; Dass, Crispin; Nurgali, K. (Elsevier Ltd., 2012)
Netrin-1 is a well-characterised chemoattractant involved in neuronal guidance in the developing enteric nervous system (ENS), but it is also a regulator of tumorigenesis. Two of its well-characterised receptors, deleted in colorectal cancer (DCC) and uncoordinated-5 homolog (UNC-5H), belong to a family of dependence receptors that transmit either pro- or anti-apoptosis signals depending on the availability of ligand, in this case netrin-1. This review summarises these two effects of netrin-1 and highlights the additional research needed information about to allow better utilisation of netrin-1 as a therapeutic target for axonal regeneration in the context of colorectal cancer.